Effects Of Pipe Curvature And Internal Pressure On Stiffness And Buckling Phenomenon Of Circular Thin-Walled Pipes - V. Polenta; S. D. Garvey; D. Chronopoulos; A. C. Long; H. P. Morvan (Zenodo, 2015)
A parametric study on circular thin-walled pipes subjected to pure bending is performed. Both straight and curved pipes are considered. Ratio D/t, initial pipe curvature and internal pressure are the parameters varying in the analyses. The study is mainly FEA-based. It is found that negative curvatures (opposite to bending moment) considerably increase stiffness and buckling limit of the pipe when no internal pressure is acting and, similarly, positive curvatures decrease the stiffness and buckling limit. For internal pressurised pipes the effects of initial pipe curvature are less relevant. Results show that this phenomenon is in relationship with the cross-section deformation due to bending moment, which undergoes relevant ovalisation for no pressurised pipes and little ovalisation for pressurised pipes. : {"references": ["S. P. Timoshenko and J. M. Gere, \"Theory of elastic stability,\" 1961.", "G. Bryan, \"On the stability of a plane plate under thrusts in its own plane,\nwith applications to the buckling of the sides of a ship,\" Proceedings of\nthe London Mathematical Society, vol. 1, no. 1, pp. 54\u201367, 1890.", "S. R. Hauch and Y. Bai, \"Bending moment capacity of pipes,\" Journal\nof Offshore Mechanics and Arctic Engineering, vol. 122, no. 4, pp.\n243\u2013252, 2000.", "K. M\u00f8rk, J. Spiten, E. Torselletti, O. Ness, and R. Verley, \"The superb\nproject and dnv'96: Buckling and collapse limit state,\" in Proceedings\nof the International Conference on Offshore Mechanics and Artic\nEngineerinng. American Society of Mechanical Engineers, 1997, pp.\n79\u201390.", "J. Hutchinson, \"Axial buckling of pressurized imperfect cylindrical\nshells,\" AIAA Journal, vol. 3, no. 8, pp. 1461\u20131466, 1965.", "H. Crate, S. Batdorf, and G. W. Baab, \"The effect of internal pressure\non the buckling stress of thin-walled circular cylinders under torsion,\"\nDTIC Document, Tech. Rep., 1944.", "A. Robertson, H. Li, and D. Mackenzie, \"Plastic collapse of pipe bends\nunder combined internal pressure and in-plane bending,\" International\nJournal of Pressure Vessels and Piping, vol. 82, no. 5, pp. 407\u2013416,\n2005.", "H. Yudo and T. Yoshikawa, \"Buckling phenomenon for straight and\ncurved pipe under pure bending,\" Journal of Marine Science and\nTechnology, 2014.", "V. Polenta, S. Garvey, D. Chronopoulos, A. Long, and H. Morvan,\n\"Optimal internal pressurisation of cylindrical shells for maximising\ntheir critical bending load,\" Thin-Walled Structures, vol. 87, pp.\n133\u2013138, 2015.\n[10] H. M. Mourad and M. Y. Younan, \"Limit-load analysis of pipe bends\nunder out-of-plane moment loading and internal pressure,\" Journal of\npressure vessel technology, vol. 124, no. 1, pp. 32\u201337, 2002.\n[11] A. Hilberink, Mechanical behaviour of lined pipe. Ph. D. Thesis, Delft\nTechnical University, ISBN 978-94-6186-012-5, 2011.\n[12] C. Thinvongpituk and S. Poonaya, \"A study of the ovalisation of\ncircular tubes subjected to pure bending,\" in Current Themes in\nEngineering Science 2008: Selected Presentations at the World Congress\non Engineering2008, vol. 1138, no. 1. AIP Publishing, 2009, pp.\n129\u2013140."]}